Droplet Digital PCR Provides Highly Sensitive and Accurate Opsin Gene SNP Detection From Wild Primate Fecal Samples - Arthur G. Fernandes; Saúl Cheves Hernández; Ronald López Navaro; Shoji Kawamura; Amanda D. Melin (Ecology and Evolution)
ABSTRACT Evaluating field‐sourced samples with poor‐quality and low‐quantity DNA, like animal feces, presents significant challenges in the field of molecular biology. Nonetheless, recent innovations in PCR technology are promoted as effective tools to overcome many of these issues. Here, we evaluate the efficiency of droplet digital PCR (ddPCR) as a method for color vision assessment from feces of white‐faced capuchins (Cebus imitator) and report frequencies of alleles and genotypes in a wild population. The sex‐linked color vision polymorphism of monkeys in the Americas is driven by single nucleotide polymorphisms (SNPs) in opsin genes at up to three tuning sites. DNA was extracted from fecal samples collected from 211 wild capuchins (53.1% males) in Sector Santa Rosa, Costa Rica: 56 were evaluated with ddPCR, 24 with both ddPCR and Sanger sequencing, and 141 with Sanger sequencing (historical dataset). The same opsins and genotypes were derived for each monkey using Sanger and ddPCR; however, the latter method was far more sensitive and required far fewer samples to reach a definitive genotype. Overall, the most frequent phenotypes were red and green/red. The distribution of genotypes was: Females (N = 99): green/red (35.4%), red/red (33.3%), green/yellow (14.1%), yellow/red (12.1%), yellow/yellow (4.0%), and green/green (1.0%); Males (N = 112): red (60.7%), yellow (23.2%), and green (16.1%). Overall, ddPCR was a reliable method for evaluating color vision noninvasively in wild capuchins with the advantage of excellent sensitivity and high‐throughput. ddPCR is highly robust to PCR inhibitors and can be potentially used to identify other disease‐related SNP mutations noninvasively in wild animals.